2000
DOI: 10.3171/jns.2000.93.4.0667
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomy of the pericallosal arterial complex

Abstract: The authors propose a logical classification of the different variations in the pericallosal arterial complex based on embryological development. This complex can be considered a hemodynamic solution to an abnormal regression of one of its parts, which is balanced by the development of supplemental channels from other parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 7 publications
0
45
0
4
Order By: Relevance
“…Two symmetrical callosomarginal arteries can also be present in the same hemisphere (78). A typical CmA has a longer course compared to the two symmetrical atypical callosomarginal arteries and usually originates from the A3 segment (28,62,78). Ugur et al (78) observed typical, atypical or absent CmA's in 49%, 34% and 17% respectively.…”
Section: Callosomarginal Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…Two symmetrical callosomarginal arteries can also be present in the same hemisphere (78). A typical CmA has a longer course compared to the two symmetrical atypical callosomarginal arteries and usually originates from the A3 segment (28,62,78). Ugur et al (78) observed typical, atypical or absent CmA's in 49%, 34% and 17% respectively.…”
Section: Callosomarginal Arterymentioning
confidence: 99%
“…Since the origin of the callosomarginal artery can vary, this terminology can be problematic (36). The CmA is also not always present and therefore it is preferable to classify the pericallosal artery as the segment distal to the AcoA (28,62). The callosomarginal artery has been observed in 40.0% to 93.4% of specimens (6,17,28,34,44,54,62,64,65,68,69,78).…”
mentioning
confidence: 99%
“…La arteria cerebral anterior (ACA) es la rama terminal anterior de la arteria carótida interna 23,35,40,42,50 . Desde su origen en el sector más interno de la cisura de Silvio, se dirige hacia delante y adentro cruzando por arriba al quiasma (70%) o el nervio óptico homolateral (30%) 35 .…”
Section: Anatomía Quirúrgica De La Acad (Figura 5)unclassified
“…The A4 segment runs superior to the corpus callosum, extending to a point just behind the coronal suture. The A5 segment is the portion of the AComA that lies posterior to the coronal suture (10).…”
Section: Anatomymentioning
confidence: 99%
“…They are uncommon, comprising only 2.7 to 9.2% (mean, 4.4% in 13 large series) of all intracranial aneurysms. (14,23,10) Their location in the interhemispheric fissure, the association with intracerebral hemorrhage, with multiple aneurysms and with vascular anomalies of the anterior cerebral artery (ACA) offer the neurosurgeon a complex pathology and challenging surgical technique. The complexity of this pathology is completed by the specific anatomic features of DACA aneurysms, such as their small size and the broad neck with originating branches at this level (14,23).…”
mentioning
confidence: 99%